The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13197-015-2006-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes of stabilizer-free natural peanut butter during storage

Abstract: The storage stability of preservative-free peanut butter was evaluated for changes in physicochemical quality including moisture content and water activity, microbiological properties, oxidative stability and textural quality in terms of spreadability and firmness. The study was conducted for 16 weeks at storage temperature of 10, 25 and 35 °C on natural and pure peanut butter produced from two varieties of peanuts, the Virginia and Spanish TMV-2 varieties of China and India origin, respectively. The peanuts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…At the end of 28 days, sample preserved with only clove extract was rated highest rating (7.13), followed by sample preserved with BHA (6.80). The result was in agreement with the findings of Mohd-Rozalli, et al [24,25], who reported 4 weeks of oxidative stability for stabilizer-free natural peanut butter at temperature of 25°C. According to the authors, storage temperature had the most significant effect on quality changes of peanut butter.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…At the end of 28 days, sample preserved with only clove extract was rated highest rating (7.13), followed by sample preserved with BHA (6.80). The result was in agreement with the findings of Mohd-Rozalli, et al [24,25], who reported 4 weeks of oxidative stability for stabilizer-free natural peanut butter at temperature of 25°C. According to the authors, storage temperature had the most significant effect on quality changes of peanut butter.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…The colloidal stability was expressed as the Oil separation according to the methods of Rozalli et al 10 . Separated oil on the surface was drained with a filter paper and its percentage was calculated via the following equation:…”
mentioning
confidence: 99%
“…In butters, fat imparts shortening effect and improves the tenderness, spreadability, mouth feel and flavour of the product [32]. The high percentage of unsaturated fatty acids in peanut oil [6,7] and in sesame seed oil [11,14,15] is considered advantageous for preventing heart diseases and controlling bad cholesterol level in human body [33,34]. In view of the fact that butter made from peanut paste and sesame seed paste consists of plant based unsaturated fats with negligible amount of trans fat [35], the product could be considered healthier alternative to dairy butter.…”
Section: Effect Of the Treatment On The Proximate Composition Of The Prepared Buttermentioning
confidence: 99%
“…Peanut butter is the most important product made from peanut in the world and it is utilized as nutritious spread for bread and crackers as well as ingredient in sandwiches, cookies, confectionaries and other products [6]. The retained high protein and unsaturated fatty acids content in peanut even after being processed into butter makes it an excellent and affordable protein and lipid source [7]. Due to its high nutritive value, peanut based ready-to-usetherapeutic food (RUTF) has been implemented in the diet programme to treat malnutrition among children in African countries [8,9].…”
Section: Introductionmentioning
confidence: 99%